Conditioning of the Process of Technology Transfer from Science into Business in Poland - Kuźniar, Katarzyna (Uwarunkowania procesu transferu technologii z nauki do biznesu w Polsce, 2009)
The goal of this paper it is to specify conditions and to assess cooperation between science and business in Poland in terms of technology transfer. In the first part of the paper the author presents a model of evolution of universities which consists of three phases of their development. Special attention is paid to the idea of third generation university, which is open to partnership form of cooperation with enterprises, and for which the third purpose of its activity is the commercialization of technology. In the second part of the article the author focuses on the sources of barriers for cooperation between universities and business in Poland and tries to work over opportunities for improvement of mutual relations of both environments in terms of use of know-how within business in practice.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 81, s. 50-57
Keywords: innovation activity; commercialization of results of scientific research; rules of efficient cooperation